The Impact of Service Quality, Facilities, and Pricing on Customer Satisfaction: A Study of Barbershop Swales in Pontianak - Herawaty, Rhesa; Fachri, Helman (Dinasti Publisher, 2024)
This study examines the influence of service quality, facilities, and pricing on customer satisfaction in Barbershop Swales, Pontianak. This research addresses the growing demands of the barbershop industry, focusing on how these three factors shape customer perceptions. A quantitative approach was used, employing a structured questionnaire distributed to 100 customers. The data were analyzed using multiple linear regression to identify both individual and collective effects of the variables on customer satisfaction. The findings reveal that while service quality positively influences satisfaction, its impact is not statistically significant. In contrast, facilities and pricing play significant roles, with pricing emerging as the most dominant factor. This suggests that customers prioritize competitive pricing and high-quality facilities over service standards when choosing barbershops. The study highlights the importance of adjusting pricing strategies and improving facilities to enhance customer satisfaction in the barbershop industry in mid-sized urban areas